KONSERVASI SUMBER DAYA AIR DAN LINGKUNGAN MELALUHI KEARIFAN LOKAL DI DESA MARGODADI KECAMATAN SEYEGAN KABUPATEN SLEMAN YOGYAKARTA - Rita Dewi Triastianti; Nasirudin Nasirudin; Sukirno Sukirno; Warsiyah Warsiyah (Universitas Gadjah Mada, 2017)
Local wisdom has been derived from the expression of ancestors that grows and develops especially in rural life norms which could be related to local food security. The question will be on what kind of natural resources can be managed without damaging the environment. In line with the issue, we need to know the local natural resources and manage it through the people behavior by following the local norms. Margodadi Village located in the western part of Sleman regency. The condition of society and its natural resources and environment is still original and unique. Activities undertaken by the community are mostly simple and traditional. Live harmony between individuals in society still exists. Natural resources and the environment are utilized by the community from generation to generation to this day, such as the existence of clean water - lake which is considered out of a big banyan tree. This water comes out of the ground under the tree and is called “Tuk Sibedug”. The water of this lake is often used for bathe rituals in a pond and the rest flows into the river for farming irrigation especially rice fields. By knowing the inner or spiritual strength of each individual, the norms of life will grow and develop, so that natural resources and environment can be managed better. Natural resources from the agricultural, livestock, fishery and small industries sectors are possible to potentially generate per capita income of 519 kg per person per year. This shows the existence of local food security in the villages of Seyegan that has been achieved.